Three-dimensional endoscopic visualization in functional endoscopic sinus surgery - Albrecht, Tobias; Baumann, Ingo; Plinkert, Peter K.; Simon, Christian; Sertel, Serkan (European archives of oto-rhino-laryngology and head & neck, 2016)
Three-dimensional (3D) stereoscopic vision in sinus surgery has been achieved with the microscope so far. The introduction of two-dimensional (2D) endoscopes set a milestone in the visualization of the surgical field and paved the way to functional endoscopic sinus surgery (FESS), although the 2D endoscopes cannot provide a stereoscopic visualization. The latest technology of 3D endoscopes allows stereoscopic vision. We provide a clinical investigation of all commercially available 3D endoscopes in FESS to compare their clinical value and efficacy to routinely used conventional 2D HD endoscopes. In this prospective, randomized, controlled clinical study, 46 patients with polypoid chronic rhinosinusitis underwent FESS with one of the following three endoscopes: 2D 0° high definition (HD), 3D 0° standard definition (SD) and 3D 0° HD. Four surgeons qualitatively assessed endoscopes on stereoscopic depth perception (SDP) of the surgeon, sharpness and brightness of the image, as well as their comfort in use during surgery. Surgeons assessed the brightness of the control (2D HD) significantly better than 3D SD (p = 0.009) and brightness of 3D HD was rated significantly better than 3D SD (p = 0.038). Stereoscopic depth perception (SDP) of 3D SD was assessed highly significantly better than the control (2D HD) (p = 0.021), whereas 3D HD displayed best SDP (p = 0.0001). The comfort in use was rated significantly higher in the 3D HD group compared to the control group (p = 0.025). No significant differences in sharpness could be seen among all endoscopes. 3D HD endoscopy provides an improvement in SDP and brightness of the surgical field. It enhances the intraoperative visualization and is therefore an important and efficient development in endoscopic sinus surgery.